POVERTY AS A CAUSE OF EARLY MARRIAGE: A LITERATURE REVIEW - Syifa Hajarul Istiqomah; Iis Rahmawati; Nurfika Asmaningrum (UPT Penerbitan Universitas Jember, 2023)
Background: Early marriage is a marriage contract which is held for children under the age of applicable regulations. 1 of 5 children in Indonesia is married. The number of women aged 20- 24 years old who were married before the age of 18 in 2018 were estimated to reach 1.220.900 and this number put Indonesia in 10 countries with the highest absolute number of child marriage in the world. Methods: The method used in this research was literature review by compiling 10 journals based on the inclusion criteria. Results: A number of socioeconomic and cultural factors such as education, adolescent pregnancy, and poverty affected early marriage. Poverty was the main driver of child marriage on women in developing countries. Conclusions: A higher poverty level increased the probability of girls to be a young bride significantly. The issue of poverty and low education level cannot be eradicated instantly, and would need persistent and comprehensive planning and regulations.